Mange Caused by Knemidocoptes mutans - Outbreak in Free-range Chickens - Souza, Isabela Pereira de Oliveira; De Oliveira, Danilo Coimbra; Santos, Marcos Wilker da Conceição; Conceição, Maurício dos Santos; Albuquerque, Milena Oliveira; Parazzi, Larissa José; dos Santos, Flavia (Acta Scientiae Veterinariae, 2024)
Background: Brazil stands out as one of the leading countries in poultry. The raising of free-range chickens is evident all over the national territory. Standing out for the rusticity of the animals, feeding and extensive management, they have free access to land and pasture area, becoming a positive aspect for animal welfare. However, the lack of adequate chicken coops and sanitary management, as well as less nutritional and reproductive rigor, will result in low productivity and lead to greater occurrences of parasitic diseases. The objective was to report an outbreak of parasitism caused by the mite Knemidocoptes mutans in free-range chickens in the municipality of Barra, Bahia, Brazil. Cases: The occurrence of mange on the legs, caused by the mite of the genus Knemidocoptes, with Knemidocoptes mutans as the direct agent, is a chronic disease that can manifest itself at any age and is linked to individual characteristics of the birds. In this report, a poultry farmer from the municipality of Barra, western Bahia, producer of free-range chickens, reported her experience when her birds were affected by the K. mutans mite. The birds presented scaly deformations on the scales of the metatarsus and feet, leaving the scales deformed and dull. The animals were raised in a semi-confined manner, having access to pasture and dirt floor, and fed with whole corn grains, water from a well and the area cleaned every 15 days. All birds had a history of vaccination against avian smallpox and Newcastle Disease. The avian lived with other species of animals and the chicken coop was formerly a pig pen for raising pigs. During the anamnesis, dermatitis, crusts and deformations of the scales were noted. The treatment was carried out topically, systemically and environmentally. Discussion: To diagnose knemidocoptic mange, patterns of skin lesions associated with laboratory techniques for microscopic visualization of the parasite are observed. The birds studied are bred in captivity for subsistence; therefore, genetic factors and the restricted lifestyle of the animals can influence the development and appearance of several diseases, as well as knemidocoptiasis. Diagnosis is restricted to morphological characteristics, predilection hosts, aspects of the lesions and sites of parasitism. Furthermore, there are few detailed descriptions of the etiopathogenesis of the disease and host susceptibility factors. Knemidokoptic mange is caused by several species of mites of the genus Knemidokoptes belonging to the family Knemidokoptidae, all parasites on the skin of birds. The specific cause of mange on the feet is Knemidocoptes mutans, a very small mite, which has a rounded body and lives inside the scales that cover the bird’s metatarsus. Thus, the characteristic lesions of knemidocoptic mange are dermatitis, crusts, deformation of the scales and the deep presence of the mite, which can be observed through microscopy of the crusts. For treatment and prophylaxis, hygiene and handling must be taken into account, recommending daily cleaning of perches and floors with chlorine and application of sulfur-based paste to the lesions. Insecticides and acaricides must also be sprayed, respecting the recommended dosages with a well-defined program, with three repetitions at an interval of 1 week each. Therefore, if management is carried out properly, after 15 days the birds already have complete elimination of the mite and improvement in the lesions on their feet. Keywords: family subsistence, ectoparasites, mite, foot mange in chickens. Título: Sarna causada por Knemidocoptes mutans - surto em criação de galinhas caipiras Descritores: subsistência familiar, ectoparasitas, ácaro, sarna podal em galinhas.